Efficacy and safety of perampanel monotherapy in patients with focal‐onset seizures with newly diagnosed epilepsy or recurrence of epilepsy after a period of remission: The open‐label Study 342 (FREEDOM Study). Issue 2 (7th June 2020) - Yamamoto, Takamichi; Lim, Sung Chul; Ninomiya, Hirotomo; Kubota, Yuichi; Shin, Won Chul; Kim, Dong Wook; Shin, Dong Jin; Hoshida, Tohru; Iida, Koji; Ochiai, Taku; Matsunaga, Risa; Higashiyama, Hiroyuki; et al.
Abstract: Objective: Our study assessed perampanel monotherapy in patients (aged ≥12 years) with focal‐onset seizures (FOS) with or without focal to bilateral tonic‐clonic seizures (FBTCS) in Japan and South Korea. Methods: Study 342 (NCT03201900; FREEDOM) is a single‐arm, open‐label, Phase III study. Patients initially received perampanel in a 32‐week 4‐mg/d Treatment Phase (6‐week Titration; 26‐week Maintenance Periods). If they experienced a seizure during the 4‐mg/d Maintenance Period, they could be up‐titrated to 8 mg/d across an additional 30‐week Treatment Phase (4‐week Titration; 26‐week Maintenance Periods). Primary endpoint was the seizure‐freedom rate during the Maintenance Period (4 mg/d and last evaluated dose [4 or 8 mg/d]). Secondary endpoints included time to first seizure onset and to withdrawal during Maintenance. Treatment‐emergent adverse events (TEAEs) were monitored. Results: At data cutoff (February 28, 2019), 89 patients with FOS (84 [94.4%] with newly diagnosed epilepsy and 5 [5.6%] with recurrence of epilepsy after a period of remission) had received ≥1 perampanel dose; 16 patients discontinued during the 4‐mg/d Titration Period, meaning 73 patients entered the 4‐mg/d Maintenance Period and were included in the primary analysis set for efficacy. Seizure‐freedom rate in the 26‐week Maintenance Period was 46/73 (63.0%; 95% confidence interval [CI]: 50.9‐74.0) at 4 mg/d and 54/73 (74.0%; 95% CI: 62.4‐83.5) at 4 or 8 mg/d. Cumulative probability of seizure‐onset and withdrawal rates during Maintenance was 30.8% (95% CI: 21.5‐43.0) and 23.7% (95% CI: 15.4‐35.3) at 4 mg/d, and 18.2% (95% CI: 11.0‐29.3) and 23.3% (95% CI: 15.2‐34.8) at 4 or 8 mg/d. Perampanel was generally well tolerated, and the most common TEAE was dizziness. Significance: Perampanel monotherapy (4 to 8 mg/d) was efficacious and consistent with the known safety profile up to 26 weeks in patients (≥12 years) with primarily newly diagnosed FOS with or without FBTCS.